From Clinical Trials to the Front Line: Vinflunine for Treatment of Urothelial Cell Carcinoma at the National Cancer Institute of Naples - Facchini, Gaetano; Della Pepa, Chiara; Cavaliere, Carla; Cecere, Sabrina C.; Di Napoli, Marilena; D'Aniello, Carmine; Crispo, Anna; Iovane, Gelsomina; Maiolino, Piera; Tramontano, Teresa; Piscitelli, Raffaele; Pisconti, Salvatore; et al. (Frontiers in Pharmacology, 2016)
Background: The efficacy of Vinflunine, after failure of platinum-based chemotherapy in patients with metastatic or recurrent Transitional Cell Cancer of the Urothelial Tract, TCCU, has been demonstrated in an international, randomized, phase III trial comparing Vinflunine plus Best Supportive Care, BSC, with BSC alone. On the basis of that study vinflunine has been approved by the European Medicine Association, EMA, for treatment of TCCU patients after failure of a platinum treatment. However, since data in clinical trials often differ from routine clinical practice due to unselected population and less strict monitoring, “real life” experiences are very helpful to verify the efficacy of a new therapy. Methods: This was a spontaneous, observational, retrospective study involving 43 patients with metastatic TCCU treated with vinflunine at our cancer center, data about demographics, disease characteristics, and previous treatments were collected and outcome and toxicities of vinflunine were analyzed. Results: 41 of 43 patients were eligible for RR analysis, the Overall RR was 12%, the Disease Control Rate was 29%; when including only patients treated in II line the DCR rose to 33%; the median PFS and the median OS were 2.2 and 6.9 months, respectively. Conclusion: Our findings were consistent with the outcome data emerged in the phase III randomized trial and in the other observational studies conducted all around Europe in the last 2–3 years. This experience supports the use of vinflunine in patients with advanced TTCU as effective and manageable antineoplastic drug.